Chemical Fractionation of Selected Nevada Soils Adjacent to the Sierra Army Depot. Issue 4 (9th July 2014) - Burt, R.; Chiaretti, J. V.; Ferguson, R.
Abstract : Parent material, pedogenic processes, and anthropogenic inputs are factors in the levels, distribution, and forms of trace elements in selected soils adjacent to the Sierra Army Depot. Anthropogenic inputs were related to a long history of burning munitions, rocket engines, and various pyrotechnics, resulting in possible soil contamination from downward deposition of metal‐bearing dust. Jaybee and Trocken soils in western Nevada were analyzed by sequential extraction of the chemical fractions of trace elements as follows: water soluble (WS), exchangeable (EX), specifically sorbed/carbonate‐bound (SS/CAR); Fe‐Mn oxide‐bound (OX), organic/sulfide‐bound (OM/S), residual (RES), and total. Study objectives were to investigate potential reactivity of trace elements to determine their (i) changes with time and depth and (ii) relationship with other soil properties as well as with other soils, both contaminated and uncontaminated. While total and fractionated trace element concentrations increased with time in all horizons, the relative predominance of fractions remained the same: OX > RES > SS/CAR > OM/S > EX > WS, suggesting some anthropogenic inputs were added as well as later transformed to OX forms. Most trace elements showed OX or RES as either the first or second most predominant fraction, indicating elements were associated with both natural as well as anthropogenic sources. Trace elements that were OX increased with time in surface horizons of Jaybee and Trocken by 5 and 1%, respectively. Water soluble trace elements was slightly smaller in Trocken (0.3–0.5%) than Jaybee (0.6–1%), with SS/CAR greater in Trocken (11–16%) than Jaybee (7–9%). Jaybee showed pH 7.6 to 7.7 and no carbonates and Trocken pH 8.9 to 9.8 and 1 to 3% carbonates. Trace element deposition and accumulation as well as metal movement within soil profiles with time were indicated despite the arid environment.